Ancient households on the north coast of Peru - Johnson, Ilana, editor; Pacifico, David, editor; Cutright, Robyn E., editor; University Press of Colorado, publisher (Colorado State University. Libraries, 2021)
Not limited to one time period or civilization, provides insight into the development of complex, urban, and state-level society in the region, showing how observed domestic patterns inform a new archaeological perspective on general processes in domestic life in and beyond Andean prehistory.--Provided by publisher.
Diverse, dynamic, and enduring: ancient households of the north coast of Peru / David Pacifico and Ilana Johnson -- New directions in household archaeology: case studies from the north coast of Peru / Brian R. Billman -- Cercaduras and domestic urban life in Early Horizon Nepeña, coastal Ancash / David Chicoine, Hugo Ikehara, and Jessica Ortiz -- Communities in motion: peripatetic households in the Late Moche Jequetepeque Valley, Peru / Guy S. Duke -- Figures of Moche past: examining identity and gender in domestic artifacts / Ilana Johnson -- Pillars of the community: Moche ceremonial architecture as symbolic household at Huaca Colorada, Jequetepeque Valley, Peru / Giles Spence Morrow -- Households and urban inequality in 14th century Peru / David Pacifico -- Continuity and change in Late Intermediate Period households on the north coast of Peru / Robyn E. Cutright -- Enduring collapse: households and local autonomy at Talambo, Jequetepeque, Perú / Kari A. Zobler -- Diversity in north coast households: rethinking the politics of the everyday / Edward Swenson.
Keywords: Indians of South America -- Peru -- Pacific Coast -- Social life and customs -- Case studies; Household archaeology -- Peru -- Pacific Coast -- Case studies; Material culture -- Peru -- Pacific Coast; Material culture -- Peru -- Pacific Coast; Indians of South America -- Peru -- Pacific Coast -- Antiquities; Dwellings, Prehistoric -- Peru -- Pacific Coast; Social archaeology -- Peru -- Pacific Coast